The Taxonomic Representation of Common Events: A Research Report - López Rousseau, Alejandro; Tappe, Heike; Habel, Christopher (Psykhe, 2004)
Shared cognitive representations have been shown in different conceptual domains.An experiment is presented here that extends this line ofresearch to the domain ofevents.Specifically, this experiment shows a cultural consensus in the participants’event taxonomies, and suggests a shared event taxonomy based on semantic relations.Showing such a shared event representation is an important first step for learning about the role of events in cognitive processes such as memoryand thought.